Increase in ozone due to the use of biodiesel fuel rather than diesel fuel. (September 2016) - Thang, Phan Quang; Muto, Yusuke; Maeda, Yasuaki; Trung, Nguyen Quang; Itano, Yasuyuki; Takenaka, Norimichi
Abstract: The consumption of fuel by vehicles emits nitrogen oxides (NOx ) and non-methane hydrocarbons (NMHCs) into the atmosphere, which are important ozone precursors. Ozone is formed as a secondary pollutant via photochemical processes and is not emitted directly into the atmosphere. In this paper, the ozone increase resulting from the use of biodiesel and diesel fuels was investigated, and the different ozone formation trends were experimentally evaluated. Known amounts of exhaust gas from a power generator operated using biodiesel and diesel fuels were added to ambient air. The quality of the ambient air, such as the initial NMHC and NOx concentrations, and the irradiation intensity have an effect on the ozone levels. When 30 cm 3 of biodiesel fuel exhaust gas (BFEG) or diesel fuel exhausted gas (DFEG) was added to 18 dm 3 of ambient air, the highest ratios of ozone increase from BFEG compared with DFEG in Japan and Vietnam were 31.2 and 42.8%, respectively, and the maximum ozone increases resulting from DFEG and BFEG compared with the ambient air in Japan were 17.4 and 26.4 ppb, respectively. The ozone increase resulting from the use of BFEG was large and significant compared to that from DFEG under all experimental conditions. The ozone concentration increased as the amount of added exhaust gas increased. The ozone increase from the Jatropha -BFEG was slightly higher than that from waste cooking oil-BFEG. Graphical abstract: Highlights: Ozone increment with the use of biodiesel fuel rather than diesel fuel. Ozone increment was evaluated by direct experimental measurement. The ozone concentration was increased with increasing amount of exhausted gas addition. Due to different ambient air composition, the trend of ozone increment between Vietnam and Japan are different. Abstract : The first ozone increment in the use of biodiesel fuel was experimentally evaluated, and compared the ozone increment between biodiesel and petroleum diesel fuel.